The effect of religiusity, social environment and levels of profit sharing on customer interest in saving at KSPPS Artha Abadi Jepara - mahmudah sa'diyah (NUsantara Islamic Economic Journal, 2023)
The purpose of this study was to determine the effect of religiosity, social environment and the level of profit sharing on the intention to saving at Islamic financial institutions KSPPS Artha Abadi Jepara. The data used in this study are primary data collected through questionnaires. The population of this study were members of KSPPS Artha Abadi Jepara, totaling 4470 people with a sample of 98 respondents. The analysis technique used in this study is to use multiple regression analysis. The results of this study indicate that simultaneously Religiosity (X1), Social Environment (X2), Level of Profit Sharing (X3) simultaneously affect the intention to save (Y) at KSPPS Artha Abadi Jepara. However, partially religiosity, social environment, and profit-sharing levels have a positive and significant effect on the intention to save at KSPPS Artha Abadi Jepara.